Cross‐cultural adaptation and psychometric evaluation of Hindi version of Diabetes Self‐Management Profile‐Self Report in Indian type 1 diabetes patients. Issue 1 (23rd July 2020) - Barola, Anjana; Tiwari, Pramil; Bhansali, Anil; Grover, Sandeep; Dayal, Devi
Abstract: Background: No validated measures exist for evaluating diabetes self‐management in Indian type 1 diabetes (T1D) patients. Objective: To cross culturally adapt and evaluate the psychometric properties of Hindi version of Diabetes Self‐Management Profile‐Self Report (DSMP‐SR‐Hindi) in Indian T1D patients. Methods: Total 160 T1D patients and their parents participated in the study. The mean age of patients was 13.5 ± 2.5 years and HbA1c was 8.6 ± 2.2%. Results: Exploratory factor analysis employing principle axis factoring with promax rotation was conducted. Monte Carlo parallel analysis identified three sub‐scales instead of five sub‐scales proposed in original version. Because of underlying ceiling and floor effects and insufficient loadings, five items were eliminated. Consequently, final Hindi version of DSMP‐SR contained 19 items from DSMP‐SR‐24. Internal consistencies were adequate for overall scale (Cronbach's α = 0.835), identified sub‐scales (Cronbach's α = 0.702‐0.802) and comparable between genders. DSMP‐19 total scores ( r = −0.74) and three subscales correlated significantly with HbA1c (SMBG and Corrective Adjustments [ r = −0.58], Exercise [ r = −0.48], and Conformity to Diet and Insulin Routine [ r = −0.64]). For every one SD improvement (11.2 marks) in DSMP‐SR‐Hindi score, odds of falling into poor glycaemic group (HbA1c > 7.5%) dropped to 0.242 times (95% CI 0.144‐0.405; P  < .001). Conclusions: DSMP‐SR‐Hindi is a reliable and valid self‐report measure of diabetes self‐management behavior in Indian T1D patients. The revealed three subscales are reliable to use in isolation and across the genders. It will help in monitoring patient's progress in stepwise manner, ranging from their basic understanding of prescribed regimen to taking advance corrective actions in face of altered needs.